Gradient metal-laser welding method for curved glass

By constructing a gradient metallization layer on curved glass and combining it with adaptive laser technology, the problems of strength, airtightness and reliability in curved glass connection are solved, achieving a connection effect with high strength, airtightness and low cracking risk, which is suitable for complex three-dimensional configurations.

CN121342372APending Publication Date: 2026-01-16JIANGSU CHINA CARBON GREEN TRANSFORMATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511750292.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing technologies cannot achieve a permanent connection between curved glass shells that is strong, airtight, and reliable. Traditional methods suffer from problems such as low mechanical strength, poor aging resistance, mismatch in thermal expansion coefficients, risk of cracking due to thermal stress, and microscopic defects.

Method used

The gradient metal-laser welding method is adopted. By constructing a gradient metallization layer on the glass surface and combining it with adaptive laser technology, a smooth transition between chemical bonding and thermal expansion coefficient is achieved. Laser scanning activation and precise scanning are used to form a dense and high-strength weld.

Benefits of technology

It achieves high strength, airtightness and reliability in curved glass connections, significantly reduces the risk of cracking, is suitable for connections of complex three-dimensional configurations, and is adaptable to high vacuum or high pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a gradient metal-laser welding method for curved glass, and belongs to the technical field of glass processing. The method comprises the following steps: pretreating a glass workpiece, performing magnetron sputtering on a high-purity chromium layer as a reactive interface layer, depositing a gradient self-metallization layer, and performing laser interface activation; coating borosilicate glass powder brazing filler metal slurry on the gradient self-metallization layer, fitting a to-be-welded area, carrying out gradient heating to 850 DEG C, carrying out gradient cooling annealing, cooling to room temperature, carrying out local processing on the to-be-welded area of the glass workpiece by adopting continuous optical fiber laser scanning, cooling, and checking whether a welding seam is qualified or not. The gradient metallization layer attached to the curved surface is constructed on the surface of the glass, interface chemical bonding and smooth transition of the thermal expansion coefficient are achieved, and three-dimensional thermal stress is effectively buffered. A self-adaptive laser process is adopted, a curved nickel layer is firstly scanned and activated to enhance wettability, then accurate scanning is carried out along a welding seam to realize structure remelting and refining, and finally a compact high-strength welding seam is formed.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of glass processing, in particular to a gradient metal-laser welding method for curved glass. BACKGROUND

[0002] The permanent connection between curved glass shells with high strength, high air tightness and high reliability is a difficult problem faced by the current manufacturing industry. The existing mainstream technical routes all have obvious limitations.

[0003] Firstly, although the organic adhesive bonding method is simple in process, it has defects such as low mechanical strength, poor aging resistance and easy to release volatile organic matter, which leads to a sharp decline in the reliability of the connection joint under long-term mechanical vibration, thermal cycling or humid heat environment, and cannot meet the absolute air tightness requirements in high vacuum or high pressure environment.

[0004] Secondly, although the traditional inorganic glass powder filler direct welding method solves the problems of temperature resistance and pollution to a certain extent, it exposes a series of essential defects in curved connection. Firstly, the inevitable difference in thermal expansion coefficient between the filler and the glass substrate will produce significant residual thermal stress in the complex curved structure during the cooling process from the molten state to room temperature, greatly increasing the risk of cracking at the connection interface or adjacent glass body. Secondly, in order to ensure the sufficient flow of the filler, the process temperature often needs to be close to or even exceed the softening point of the substrate glass, which easily leads to irreversible thermal deformation and optical surface distortion of the precise curved shell. Thirdly, the wettability and flowability of the molten glass filler on the glass substrate are difficult to control, and it is difficult to achieve complete and uniform filling in the three-dimensional curved gap, which is easy to produce microscopic defects such as incomplete welding and porosity.

[0005] Finally, the metal layer prepared by the traditional method has weak bonding force with the glass substrate, mainly by mechanical fitting, which is easy to peel off from the interface under thermal stress. At the same time, the large mismatch in thermal expansion coefficient between the metal filler and the glass, as well as the intrinsic non-wetting property of the filler to the glass surface, makes it difficult to implement this technical path.

[0006] Therefore, there is an urgent need for a method to realize high-quality and reliable connection between curved glass shells. SUMMARY

[0007] The purpose of the present application is to provide a gradient metal-laser welding method for curved glass, which realizes the interface chemical bonding and the smooth transition of the thermal expansion coefficient by constructing a gradient metallization layer conforming to the curved surface on the glass surface, effectively buffering the three-dimensional thermal stress. By using the adaptive laser process, the curved nickel layer is first scanned and activated to enhance the wettability, and then scanned along the weld seam to realize the organization remelting and refinement, and finally form a dense high-strength weld.

[0008] Based on the above purpose, the application provides a gradient metal-laser welding method for curved glass, comprising the following steps: (1) Put the glass workpiece into the ultrasonic cleaning machine containing analytical pure acetone and anhydrous ethanol in sequence, and clean for 15 minutes to completely remove organic contaminants; after rinsing with deionized water, dry with high-purity nitrogen; (2) After depositing a high-purity chromium layer as a reactive interface layer on the glass workpiece to be welded by magnetron sputtering, deposit a gradient self-metalization layer and then perform laser interface activation; (3) Use a precision dispensing machine to evenly apply borosilicate glass powder solder paste to the gradient self-metalization layer, and then bond the glass workpieces to be welded; under a high-purity argon environment, gradually heat to 850 DEG C, and then gradually cool and anneal; after cooling to room temperature, remove the glass workpiece when the temperature drops to below 60 DEG C; (4) Then locally process the glass workpiece to be welded by using continuous fiber laser scanning, and check whether the weld is qualified after cooling.

[0009] Preferably, step (1) further comprises placing the glass workpiece in an oxygen plasma cleaning machine after drying, with a power of 500 W, an oxygen flow rate of 200 sccm, and a processing time of 120 seconds.

[0010] Preferably, the gradient self-metalization layer in step (2) comprises a titanium layer, a nickel layer, and a copper-silver alloy layer deposited in sequence on the high-purity chromium layer.

[0011] The titanium layer, the chromium layer, and the nickel layer all form solid solutions and effectively prevent the diffusion of copper and silver; the nickel layer ensures the mechanical integrity of the entire metalization layer through its high strength and density. By introducing high-density crystal defects, a high surface energy state is obtained, thereby significantly improving the wettability with the subsequent solder. Meanwhile, the copper-silver alloy layer as the soldering participation layer can be melted together with the glass powder solder during the subsequent laser soldering process, forming the final composite weld metal. In addition, the alloy has good plasticity, which can effectively relax part of the thermal stress through plastic deformation during the cooling process, reducing the risk of interface cracking.

[0012] Preferably, in step (2), the magnetron sputtering of the high-purity chromium layer uses a high-purity chromium target as the target material, in an argon and oxygen mixed atmosphere, with a background vacuum of 5x10 -6 mbar, a working gas pressure of 0.3 Pa, a sputtering power of 500 W, a deposition time of 3-5 minutes, and a deposition thickness of 10-30 nm.

[0013] Preferably, the gradient self-metalization layer is deposited in an argon atmosphere, and the deposition conditions are as follows: Use a titanium target as the target material, with a power of 600 W, deposit for 3-6 minutes, and the titanium layer has a thickness of 20-50 nm; The nickel target is used as the target material, the power is 600W, and the nickel layer has a thickness of 90-100nm after being deposited for 5-8 minutes; The Cu80Ag20 alloy target is used as the target material, the power is 550W, and the Cu-Ag alloy layer has a thickness of 180-220nm after being deposited for 10-12 minutes.

[0014] Preferably, in the step (2), the laser interface activation atmosphere is N2 / H2 mixed gas, the laser wavelength is 500-550nm, the average power is 8-10W, the scanning speed is 100mm / s, and the light spot overlapping rate is 70%. The laser interface activation process in this embodiment induces a large number of crystal boundaries, dislocations and other micro defects on the surface of the nickel layer, so as to increase the chemical activity and roughness of the surface. In the reducing atmosphere, the laser can also remove the trace oxides on the surface to expose the pure metal surface. The laser energy can effectively penetrate and activate the defects of the nickel layer, but is insufficient to melt or ablate the copper-silver alloy on the surface layer.

[0015] Preferably, in the step (3), the gradient temperature rising is specifically performed at a rate of 5℃ / min from room temperature to 400℃ and is kept for 30 minutes, so as to completely remove the organic matter in the brazing filler metal slurry. Then, the temperature is raised to 850℃ at a rate of 3℃ / min and is kept for 45 minutes.

[0016] Preferably, in the step (4), the continuous fiber laser scanning parameters are as follows: wavelength 1070nm, power 60W, light spot diameter 75μm, and scanning speed 10mm / s. This step realizes local super-high temperature and rapid solidification. The laser energy causes the surface layer of the Cu-Ag alloy to melt together with the glass powder brazing filler metal, wets the activated nickel layer under the capillary action, fills the micro gaps on the nickel layer, and is rapidly cooled after the laser scanning, so as to form a composite weld with small grains, high density and uniformity.

[0017] Preferably, in the step (3), the gradient temperature reduction annealing is specifically performed as follows: The temperature is slowly cooled to 600℃ at a rate of 2℃ / min from 850℃; The temperature is cooled to 400℃ at a rate of 5℃ / min from 600℃; The temperature is naturally cooled to below 150℃ from 400℃.

[0018] Preferably, in the step (3), the borosilicate glass powder brazing filler metal slurry includes 85-92wt% of borosilicate glass powder, 3-5wt% of copper oxide-nickel oxide composite powder, 4.5-9.5wt% of α-terpineol and 0.5-1.0wt% of ethyl cellulose.

[0019] Therefore, the present application has the following beneficial effects: 1、The present application solves the weak interface problem in curved surface connection by forming Cr-O-Si chemical bond between the chromium layer and the curved glass and constructing a three-dimensional transition structure with the gradient metal layer, so that the joint strength approaches the glass body, and a durable airtight seal is achieved on the curved shell.

[0020] 2、The present application effectively absorbs and disperses anisotropic shrinkage stress by using the functional gradient metal layer as a multi-dimensional stress buffer zone, significantly reduces the cracking risk during curved glass connection, and greatly improves the connection yield of complex three-dimensional structures.

[0021] 3、The present application realizes full reaction at the interface while precisely scanning the curved weld joint in a three-dimensional path through the synergistic process of global processing in an atmosphere furnace and local precision machining by laser, which optimizes the microstructure and precisely controls the heat affected zone in a local area, and is especially suitable for connecting curved glass shells with limited connection area.

[0022] The technical solutions of the present application will be further described in detail through examples. DETAILED DESCRIPTION

[0023] The technical solutions of the present application will be further described in detail through examples.

[0024] Unless otherwise defined, the technical terms or scientific terms used in the present application shall have the usual meanings understood by those skilled in the art to which the present application belongs.

[0025] In addition, it should be understood that although the present specification is described in terms of embodiments, each embodiment does not contain only one independent technical solution, and the description of the specification is only for the sake of clarity, and those skilled in the art should consider the specification as a whole, and the technical solutions in each example can be appropriately combined to form other embodiments that those skilled in the art can understand. These other embodiments are also covered by the protection scope of the present application.

[0026] Example 1 The present embodiment provides a gradient metal-laser welding for curved glass, comprising the following steps: (1) Workpiece pretreatment: take two glass workpieces to be connected with a size of 100mm x 50mm and a curvature radius R=200mm, and sequentially place them in analytical pure acetone and anhydrous ethanol for ultrasonic cleaning for 15 minutes each; after rinsing with deionized water, dry them with high-purity nitrogen; place the clean workpieces into an oxygen plasma cleaning machine, and process them under the conditions of a power of 500W and an oxygen flow of 200sccm for 120 seconds to obtain an activated surface.

[0027] (2) Gradient metalization layer preparation: place the workpieces in a magnetron sputtering device, and pump the background vacuum to 5x10 -6mbar; 40 sccm of Ar and 5 sccm of O2 mixed gas was introduced, and the working pressure was maintained at 0.3 Pa; a 99.99% high-purity chromium target was used for sputtering at a power of 500 W for 4 min to form a CrO layer with a thickness of about 20 nm x Interface layer. The atmosphere was converted to a pure argon atmosphere, and a titanium target was first used for sputtering at a power of 600 W for 5 min to deposit a layer with a thickness of about 35 nm; then a nickel target was used for sputtering at a power of 600 W for 7 min to deposit a layer with a thickness of about 95 nm; finally, a copper-copper silver alloy layer was deposited by using a Cu80Ag20 alloy target for sputtering at a power of 550 W for 11 min to deposit a layer with a thickness of about 200 nm. The workpiece was transferred to a treatment chamber filled with a 5% H2 / N2 mixed gas; a 532 nm nanosecond pulsed laser was used to scan at an average power of 9 W, a speed of 100 mm / s, and a spot overlap rate of 70%.

[0028] (3) Preliminary homogenization connection: a precision dispensing machine was used to apply a borosilicate glass solder paste with a composition of 88 wt% glass powder, 4 wt% CuO-NiO composite powder, 7.2 wt% a-terpineol, and 0.8 wt% ethyl cellulose to the metallized area; after the two workpieces were aligned and attached, they were placed in a high-temperature atmosphere furnace and subjected to a heat cycle under the protection of high-purity argon: increased to 400°C at a rate of 5°C / min and held for 30 min, and the glue was removed; increased to 850°C at a rate of 3°C / min and held for 45 min for interface reaction and solder melting; slowly cooled to 600°C at a rate of 2°C / min, then cooled to 400°C at a rate of 5°C / min for stress relaxation; finally naturally cooled to 150°C in the furnace and taken out, and left to stand at room temperature until below 60°C.

[0029] (4) Laser local reinforcement treatment: a 1070 nm continuous fiber laser was used to perform secondary scanning on the weld area at a power of 60 W, a spot diameter of 75 μm, and a scanning speed of 10 mm / s; after laser treatment, the workpiece was air-cooled to room temperature to form a grain-refined composite weld.

[0030] Example 2 This example provides a gradient metal-laser fusion welding for a curved glass, including the following steps: (1) Workpiece pretreatment: two curved glass elements with a size of 50 mm x 30 mm and a curvature radius R = 150 mm were taken, and were sequentially ultrasonically cleaned in acetone and ethanol for 15 min each, rinsed with deionized water, and dried with nitrogen. Then, surface activation was completed by treatment in an oxygen plasma cleaning machine (500 W, 200 sccm O2) for 120 s.

[0031] (2) Gradient metallization layer preparation: the workpiece was placed in a magnetron sputtering device, and a 5 x 10-6 mbar background vacuum, Ar / O2 mixed gas (40 / 5 sccm) was introduced, and a 15 nm thick CrO x layer was obtained by sputtering with a chromium target at 0.3 Pa working pressure and 500 W power for 3.5 minutes. The atmosphere was converted to pure argon atmosphere, and a titanium target was first sputtered at 600 W for 4 minutes to deposit a thickness of about 30 nm; then a nickel target was sputtered at 600 W for 6 minutes to deposit a thickness of about 90 nm; finally, a copper-copper silver alloy layer was deposited by sputtering with a Cu80Ag20 alloy target at 550 W for 10 minutes to deposit a thickness of about 180 nm.

[0032] Then, in a 5% H2 / N2 atmosphere, a 532 nm nanosecond pulsed laser was used to scan at an average power of 8 W, a speed of 100 mm / s, and a spot overlap rate of 70%.

[0033] (3) Preliminary homogenization connection: using a brazing paste with a composition of 86wt% glass powder, 4wt% CuO-NiO composite powder, 9.2wt% α-terpineol, and 0.8wt% ethyl cellulose, the workpiece was assembled by dispensing, and then the following process was performed under argon protection: increased to 400°C at a rate of 5°C / min and held for 30 minutes; increased to 850°C at a rate of 3°C / min and held for 45 minutes; cooled to 600°C at a rate of 2°C / min, then to 400°C at a rate of 5°C / min, and cooled to 150°C in the furnace; and left to stand at room temperature until the temperature was below 60°C.

[0034] (4) Laser strengthening: a 1070 nm laser was used to perform secondary scanning on the weld area with a power of 60 W, a spot diameter of 75 μm, and a scanning speed of 10 mm / s; after laser treatment, the workpiece was air-cooled to room temperature to form a composite weld with refined grains.

[0035] After scanning the weld and air-cooling, the detection showed that the helium leakage rate was <5×10 -11 mbar·L / s, the tensile strength was 48 MPa, and the thermal shock test (-55°C~125°C) was 500 times without failure.

[0036] Example 3 This example provides a gradient metal-laser fusion for a curved glass, including the following steps: (1) Workpiece pretreatment: a curved glass with a size of 200 mm×100 mm and a curvature radius R=500 mm was treated in a reinforced oxygen plasma (500 W, 250 sccm O2) for 150 seconds after two-stage ultrasonic cleaning to ensure uniform activation of the large-size surface.

[0037] (2) The conditions for preparing the gradient metallization layer are the same as in Example 1, except that the CrO xThe layer sputtering parameters are 500 W, the time is 4.5 minutes, and the thickness is 25 nm; The titanium layer is sputtered at a power of 600 W for 6 minutes, and the thickness is 50 nm; The nickel layer is sputtered at a power of 600 W for 8 minutes, and the thickness is 100 nm; The Cu-Ag layer is sputtered at a power of 550 W for 12 minutes, and the thickness is 220 nm.

[0038] Subsequently, a 550 nm laser (10 W, 100 mm / s, 70% overlap) is used for processing in 5% H2 / N2.

[0039] (3) Preliminary homogenization connection: using a brazing paste with a composition of 90wt% glass powder, 3wt% CuO-NiO composite powder, 6.5wt% a-terpineol, and 0.5wt% ethyl cellulose, a large-area coating is performed under argon protection: 5℃ / min to 400℃ for 40 minutes; 3℃ / min to 850℃ for 50 minutes; 1.5℃ / min to cool to 600℃; 4℃ / min to 400℃, then furnace cooling.

[0040] (4) Laser local reinforcement treatment: a 1070 nm continuous fiber laser is used, with a power of 65 W, a spot diameter of 80 μm, and a scanning speed of 8 mm / s, and the weld area is scanned twice; after laser treatment, air cooling to room temperature forms a grain-refined composite weld.

[0041] Comparative Example 1 This comparative example provides a fusion method for curved glass, including the following steps: (1) Workpiece pretreatment: the same as step (1) of Example 1.

[0042] (2) Gradient metallization layer preparation: only a layer of 150 nm chromium is magnetron sputtered on the workpiece, and the parameters are the same as CrO x The interface layer sputtering parameters are the same, and the time is correspondingly extended.

[0043] (3) Homogenization connection: the same as step (3) of Example 1.

[0044] Comparative Example 2 This comparative example uses organic glue to bond the workpieces to be connected.

[0045] (1) Workpiece pretreatment: the workpiece is ultrasonically cleaned with acetone and ethanol and dried with nitrogen.

[0046] (2) Adhesive process: Select commercially available epoxy structural adhesive, evenly coated on a piece of glass workpiece to be connected area, with another workpiece alignment, apply light pressure. Curing at room temperature for 24 hours, and then post-cured at 80 DEG C oven for 2 hours.

[0047] The performance of the workpiece is detected, and the detection results are shown in Table 1: Table 1 Performance test results

[0048] Based on the above performance test comparison, three embodiments in helium mass spectrum leak rate (<1x10 -10 mbar·L / s), tensile strength (>40 MPa) and heat resistance (>850 DEG C) and other key indicators are excellent, and the fracture occurs in the glass body rather than the connection interface, which proves that the connection strength has exceeded the strength of the glass itself. In contrast, Example 1 fails early due to insufficient interfacial bonding force and thermal stress mismatch; Example 2 is limited by the nature of organic materials, and the performance deteriorates rapidly in a high temperature and high humidity environment.

[0049] Therefore, the present application discloses a gradient metal-laser fusion welding method for curved glass, which forms a firm chemical bond between the glass matrix and the metal weld by constructing a gradient metallization interface closely fitted with the curved shape, realizes a smooth transition of the thermal expansion coefficient, and effectively reduces the three-dimensional thermal stress generated by uneven shrinkage in each direction when the curved connector cools down. At the same time, a laser processing technology that can adapt to three-dimensional curved surfaces is adopted, which first fully scans and activates the curved nickel layer, so that the entire three-dimensional interface obtains a uniform high-activity surface, significantly improving the spreadability of the filler metal; then precise secondary laser scanning is carried out along the curved weld path, which promotes the re-melting of the weld structure and forms a fine and uniform crystal structure, and finally a dense and complete composite weld is obtained on the complex curved surface profile.

[0050] The above only describes the preferred embodiments of the present application, and it should be noted that for ordinary skilled in the art, without departing from the principles of the present application, a number of improvements and refinements can be made, which should be considered as the protection scope of the present application.

Claims

1. A gradient metal-laser fusion method for curved glass, characterized in that, The method comprises the following steps: (1) sequentially placing the glass workpiece into an ultrasonic cleaning machine containing analytical pure acetone and anhydrous ethanol, and ultrasonic cleaning for 15 minutes to completely remove organic contaminants; rinsing with deionized water and then blowing dry with high-purity nitrogen; (2) after magnetron sputtering a high-purity chromium layer as a reactive interface layer on the glass workpiece to be welded, depositing a gradient self-metalization layer and then performing laser interface activation; (3) using a precision dispensing machine to apply borosilicate glass solder paste to the gradient self-metalization layer, and then bonding the glass workpieces to be welded; under a high-purity argon environment, the temperature is gradually increased to 850℃, and then gradually decreased to anneal; when the temperature is reduced to below 60℃, the glass workpiece is taken out; (4) subsequently, locally processing the glass workpiece to be welded by using continuous fiber laser scanning, and then checking whether the weld is qualified after cooling.

2. A method for gradient metal-laser fusion welding of curved glass according to claim 1, characterized in that, In step (1), after the glass workpiece is blown dry, it is placed in an oxygen plasma cleaning machine, with a power of 500W, an oxygen flow rate of 200sccm, and a processing time of 120 seconds.

3. A method for gradient metal-laser fusion welding of curved glass according to claim 1, wherein, In step (2), the gradient self-metalization layer comprises a titanium layer, a nickel layer and a copper-silver alloy layer deposited on the high-purity chromium layer in sequence.

4. The method of claim 1, wherein the method is a gradient metal-laser fusion method for curved glass. In step (2), the magnetron sputtering of the high-purity chromium layer uses a high-purity chromium target as the target material, in an argon and oxygen mixed atmosphere, with a background vacuum of 5 x 10 -6 mbar, a working pressure of 0.3 Pa, a sputtering power of 500 W, a deposition time of 3-5 minutes, and a deposition thickness of 10-30 nm.

5. A method for gradient metal-laser fusion welding of curved glass according to claim 3, wherein The gradient self-metalization layer is deposited in an argon atmosphere, and the deposition conditions are as follows: using a titanium target as the target material, a power of 600W, depositing for 3-6 minutes, and a titanium layer thickness of 20-50nm; using a nickel target as the target material, a power of 600W, depositing for 5-8 minutes, and a nickel layer thickness of 90-100nm; using a Cu80Ag20 alloy target as the target material, a power of 550W, depositing for 10-12 minutes, and a Cu-Ag alloy layer thickness of 180-220nm.

6. The method of claim 1, wherein the method is a gradient metal-laser fusion method for curved glass. In step (2), the atmosphere for laser interface activation is N2 / H2 mixed gas, the laser wavelength is 500-550nm, the average power is 8-10W, the scanning speed is 100mm / s, and the light spot overlap rate is 70%.

7. The method of claim 1, wherein the method is a gradient metal-laser fusion method for curved glass. In step (3), the gradient temperature increasing is specifically as follows: increasing from room temperature to 400℃ at a rate of 5℃ / min, and maintaining for 30 minutes to completely remove organic matter in the solder paste; then increasing to 850℃ at a rate of 3℃ / min, and maintaining for 45 minutes.

8. The method of claim 1, wherein the method is a gradient metal-laser fusion method for curved glass. In step (4), the parameters of continuous fiber laser scanning are as follows: wavelength 1070nm, power 60W, light spot diameter 75μm, and scanning speed 10mm / s.

9. The method of claim 1, wherein the method is a gradient metal-laser fusion method for curved glass. In step (3), the gradient temperature decreasing for annealing is specifically as follows: slowly cooling from 850℃ to 600℃ at a rate of 2℃ / min; cooling from 600℃ to 400℃ at a rate of 5℃ / min; naturally cooling from 400℃ to below 150℃ in the furnace.

10. The method of claim 1, wherein the method is a gradient metal-laser fusion method for curved glass. In step (3), the borosilicate glass solder paste comprises 80-90wt% of borosilicate glass powder, 3-5wt% of copper oxide-nickel oxide composite powder, 4.5-9.5wt% of α-terpineol, and 0.5-1.0wt% of ethyl cellulose.